2020
DOI: 10.1002/jcp.30112
|View full text |Cite
|
Sign up to set email alerts
|

Association of vaspin rs2236242 gene variants and circulating serum vaspin concentrations with coronary artery disease in a Turkish population

Abstract: Coronary artery disease (CAD) is the primary cause of death worldwide. Vaspin was a recently described adipokine, playing a protective role in many metabolic and cardiovascular diseases. This study aimed to assess the relation of serum vaspin levels and vaspin rs2236242 polymorphisms with CAD. The study included 105 healthy subjects and 105 CAD patients. Serum vaspin concentrations and vaspin rs2236242 polymorphisms were determined by enzyme‐linked immunosorbent assay and polymerase chain reaction, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In another study on its association with coronary artery disease, there was a significant correlation between the AT genotype and coronary artery disease, while the TT genotype was more frequent in controls. When compared in terms of plasma vaspin levels, the TT genotype had relatively higher vaspin levels than the AT genotype, but as there were only three patients with the AA genotype, the analysis was weak ( 14 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In another study on its association with coronary artery disease, there was a significant correlation between the AT genotype and coronary artery disease, while the TT genotype was more frequent in controls. When compared in terms of plasma vaspin levels, the TT genotype had relatively higher vaspin levels than the AT genotype, but as there were only three patients with the AA genotype, the analysis was weak ( 14 ).…”
Section: Discussionmentioning
confidence: 97%
“…Studies of vaspin rs2236242 (rs6242) single nucleotide polymorphism (SNP) demonstrated that individuals carrying the A allele had higher risk of developing type 2 diabetes mellitus ( 13 ). In another recent study, patients with the vaspin A allele were also found to be at higher risk of developing coronary artery disease ( 14 ). However, the serum vaspin level was not associated with genotype frequency in either of these studies.…”
Section: Introductionmentioning
confidence: 99%
“…This also suggests that ezetimibe not only has lipid lowering effects, but also may have protective effects on vascular endothelial cells and myocardium and in addition, it may improve endothelial function and reduce cardiomyocytes apoptosis, thereby controlling the atherosclerotic process in patients with CHD. Vaspin is one of the highly expressed adipocytokines in visceral fat, whose levels are inversely related to the risk of atherosclerosis, hypertension and stroke, and their levels can also be used to reflect the degree of lipid lowering effect [17] .…”
Section: Resultsmentioning
confidence: 99%